Why We Should Be Concerned about Methicillin-Resistant Staphylococcus aureus (MRSA) - Austin B. Mogen; Kelly C. Rice (EDIS, 2016)
Treatment and complete resolution of MRSA infections can be extremely challenging, since many MRSA strains are multidrug-resistant. This 6-page fact sheet provides an overview of MRSA, different strains, risk factors, symptoms, prevention, and the pathogen’s effects on human health and agriculture. Written by Austin B. Mogen and Kelly C. Rice, and published by the UF Department of Microbiology and Cell Science, September 2015.